2013
DOI: 10.1002/jgrd.50145
|View full text |Cite
|
Sign up to set email alerts
|

Future change of the global monsoon revealed from 19 CMIP5 models

Abstract: [1] The variability of global monsoon area (GMA), global monsoon precipitation (GMP), and global monsoon intensity (GMI) in the present climate and the future warmer climate under Representative Concentration Pathways 4.5 (RCP4.5) scenario was examined based on 19 Coupled Model Intercomparison Project Phase 5 (CMIP5) simulations. In the present-day simulations, the ensemble mean precipitation reproduces the observed GMA, GMP, and GMI, although the spread of individual models is large. In the RCP4.5 simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 45 publications
6
109
0
Order By: Relevance
“…From a global perspective, the coverage and intensity of monsoon precipitation has been verified by previous studies (Wang and Xu 1997;Zhou et al 2008;Hsu et al 2011;Hsu et al 2012;Hsu et al 2013;Lee and Wang 2014). As the largest monsoon system over the world, the variability of Asian summer monsoon (ASM) has also drawn a lot of attentions (Webster et al 1998).…”
Section: Introductionmentioning
confidence: 70%
“…From a global perspective, the coverage and intensity of monsoon precipitation has been verified by previous studies (Wang and Xu 1997;Zhou et al 2008;Hsu et al 2011;Hsu et al 2012;Hsu et al 2013;Lee and Wang 2014). As the largest monsoon system over the world, the variability of Asian summer monsoon (ASM) has also drawn a lot of attentions (Webster et al 1998).…”
Section: Introductionmentioning
confidence: 70%
“…This resolution was chosen to match the spatial resolution of the satellite observations. Bilinear interpolation is a common method for interpolating precipitation (Chen and Frauenfeld, 2014;Hsu et al, 2013;Qu et al, 2013). Crow et al (2012) demonstrated that large-scale spatial patterns of soil moisture are dominated by precipitation.…”
Section: Cmip5 Modelsmentioning
confidence: 99%
“…Fundamental questions, such as what controls the location and the seasonal evolution of the EASM front, or why maximum rainfall is not colocated with maximum SSTs, remain largely unanswered. Finding answers to these questions is even more pressing in the face of the predicted expansion of subtropical dry zones with climate change, with potentially significant impacts on subtropical precipitation fronts such as the EASM, and enhanced regional sensitivity to greenhouse gases and aerosol radiative forcing (e.g., Hirahara et al 2012;Hsu et al 2013). In this paper, we attempt to address some of these questions, and we specifically focus on the mechanisms through which the TP affects the formation and seasonality of the EASM.…”
Section: Introductionmentioning
confidence: 99%